2013
DOI: 10.1039/c3cp52760c
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the coexistence of two tautomers of 2-mercaptothiazoline on the Ge(100) surface

Abstract: We confirmed the coverage dependent variation of tautomers of 2-mercaptothiazoline (the thiolate and thione forms) adsorbed on the Ge(100) surface under UHV conditions by using HRXPS measurements in conjunction with the DFT calculation method, which was studied before only in aqueous systems. The C 1s, S 2p, and N 1s core-level spectra obtained using HRXPS revealed the simultaneous presence of two distinct adsorption structures in different proportions at both low (0.15 ML) and high (0.65 ML) coverages. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We observed a double peak corresponding to S 2 p 3/2 (162.0 eV) and 2 p 1/2 (163.2 eV), separated by a spin‐orbit splitting of 1.2 eV (Figure 2a), where the S 2 p 3/2 peak is commonly used to analyze the S 2 p spectrum. The previous studies have reported that S 2 p 3/2 signals observed in the range 161.7–162.0 eV on the Ge(100) surface have been attributed to the S−H dissociated structures because a sulfur atom exists as neutral [12,17,25,26] . Therefore, based on prior results, we propose that 1‐propanethiol is adsorbed on the Ge(100) surface through S−H dissociation.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…We observed a double peak corresponding to S 2 p 3/2 (162.0 eV) and 2 p 1/2 (163.2 eV), separated by a spin‐orbit splitting of 1.2 eV (Figure 2a), where the S 2 p 3/2 peak is commonly used to analyze the S 2 p spectrum. The previous studies have reported that S 2 p 3/2 signals observed in the range 161.7–162.0 eV on the Ge(100) surface have been attributed to the S−H dissociated structures because a sulfur atom exists as neutral [12,17,25,26] . Therefore, based on prior results, we propose that 1‐propanethiol is adsorbed on the Ge(100) surface through S−H dissociation.…”
Section: Resultsmentioning
confidence: 56%
“…The previous studies have reported that S 2p 3/2 signals observed in the range 161.7-162.0 eV on the Ge(100) surface have been attributed to the SÀ H dissociated structures because a sulfur atom exists as neutral. [12,17,25,26] Therefore, based on prior results, we propose that 1-propanethiol is adsorbed on the Ge(100) surface through SÀ H dissociation. In the C 1s spectrum (Figure 2d), a single peak at 284.6 eV was observed.…”
Section: Resultsmentioning
confidence: 82%
“…2-Mercaptothiazoline (2-MT) is a heterocyclic organic compound with two tautomeric forms including a thione form (1,3-thiazolidine-2-thione) and a thiol form (2-thiazoline-2-thiol) [10] (Scheme 1), and 1,3-thiazolidine-2-thione is the predominant form in aqueous solution [11]. Due to its electron donor properties derived from –(NH)–(C=S)– group, 2-MT has been widely used in many fields [12].…”
Section: Introductionmentioning
confidence: 99%
“…Research on sulfur‐containing molecules adsorbed on the Ge(100) surface and their relevancy has revealed that thiol (SH) groups are useful in photo‐induced detectors because their reactions may be induced by photoexcitation with light of 510 nm . Owing to this characteristic, applications on the Ge(100) surface have been developed by many groups .…”
Section: Introductionmentioning
confidence: 99%